Total Energy Loss of a Test Charge in a Collisional Magnetoplasma - Shukla P.K.; Singh R.N. (My University, 2025)
Total energy loss of a test charge in a collisional magnetoplasma. P. K. Shukla (Department of Plasma Physics, Institute of Physics, Umeå University, Umeå, Sweden) and R. N. Singh (Applied Physics Section, Institute of Technology, Banaras Hindu University, Varanasi 5, India). Physica Scripta (Sweden) 4, 281-289, 1971. A general theory of energy attenuation of a charged test particle in a cold, collisional plasma has been developed. The effect of collisions on the plasma properties have been investigated. The radiation characteristics of a spiralling test particle are discussed. In the presence of collisions it is found that absorption is important when the collision frequency is comparable to the wave frequency. Estimates of radiated and absorbed power by test charges of different energies have been made, and the role of collisions on the power spectrum has been studied in detail. © 1971 IOP publisher Ltd.